(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
This paper is a comprehensive review related to the biological degradation of phenol by microorganisms. The aromatic compound, phenol or hydroxybenzene, is produced industrially or naturally. Many microorganisms that are able to biodegrade phenol have been isolated and at the same time, the metabolic pathways responsible for these metabolic processes have been determined. A large number of bacteria were studied in detail especially, pure cultures as well as the pathways of aerobic phenol metabolism and the enzymes involved. Phenol oxygenation occurred as the initial steps through phenol hydroxylase enzymes leading to formation of catechol, pursued by the splitting of the adjacent ring or in between the two groups of catechol hydroxyls. Thus, the physical and chemical environments plus the chemical structures that affecting biodegradation processes are important determining factors for combating of pollution. This nature of chemical structure for the other aromatic compounds is also a main decisive factor of biodegradability.